The Role of Benchmarking in Achieving Competitive Advantage of Egyptian Education Faculties Programs - Mohammed, Magdy Abd Elrhman Abdallah (Richtmann Publishing, 2021)
The study aimed to identify the concept and types of benchmarking, and to determine the Justifications of choosing benchmarking approach in order to achieve the competitive advantage for Egyptian Education Faculties programs, and also determine the performance indicators for Egyptian Education Foundations programs that can be used when benchmarking with the corresponding programs. The study depended on the descriptive research approach in achieving its objectives and answering its various questions and manipulating its different approaches. The study constructed a suggested model that can be used when benchmarking to Egyptian Education Faculties Programs with its distinct corresponding Programs. The study also showed the complementary relationship between benchmarking and performance indicators and their role in diagnosing an aspect of the competitive reality in the Egyptian Education Faculties programs. Received: 18 February 2021 / Accepted: 15 April 2021 / Published: 17 May 2021